2015
DOI: 10.1055/s-0035-1559666
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Pilot Study for Analysis of Antidepressant Serum Concentrations of Citalopram and Venlafaxine during Inflammation

Abstract: There was no major effect of inflammation on the metabolism of citalopram and venlafaxine. Because of the broad therapeutic indices of these 2 drugs, the drugs seem to be a good choice for the treatment of depression, even if an infection occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Other authors have also suggested that acute inflammation does not impact on CYP2D6 activity, as well as diabetes (type I, type II, and gestational). 32,33,[44][45][46] In a study conducted in patients with congestive heart failure, TNF-α and IL-6 levels were furthermore not associated with CYP2D6 activity. 29 However, another study showed that CYP2D6 activity (mean urinary dextromethorphan ratio for 4 consecutive days) was significantly higher in HIV-infected patients than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other authors have also suggested that acute inflammation does not impact on CYP2D6 activity, as well as diabetes (type I, type II, and gestational). 32,33,[44][45][46] In a study conducted in patients with congestive heart failure, TNF-α and IL-6 levels were furthermore not associated with CYP2D6 activity. 29 However, another study showed that CYP2D6 activity (mean urinary dextromethorphan ratio for 4 consecutive days) was significantly higher in HIV-infected patients than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…We described that CYP2D6 activity did not change significantly in the first 3 days after surgery, but a trend for a 50% decrease was noted at discharge, and inversely correlated with surgery and TNF‐α levels. Other authors have also suggested that acute inflammation does not impact on CYP2D6 activity, as well as diabetes (type I, type II, and gestational) 32,33,44–46 . In a study conducted in patients with congestive heart failure, TNF‐α and IL‐6 levels were furthermore not associated with CYP2D6 activity 29 .…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, no impact of the CRP value was observed on the pharmacokinetics of quetiapine in the same study. Concerning antidepressant drugs, one retrospective comparative study showed that the CRP concentration was not associated with the pharmacokinetics of citalopram or venlafaxine ( Hefner, Shams, 2015 ; Hiemke et al, 2018 ). These results confirm a different impact of inflammation on psychotropic drug metabolism depending on the CYP isoform and their respective contribution in the drug clearance.…”
Section: Pharmacological Consequences Of Acute Inflammation-induced Mmentioning
confidence: 99%
“…One exception is that the half-life of fluoxetine was significantly reduced when peginterferon-α-2b was added, indicating an accelerated depletion of fluoxetine [ 32 ]. Another recent investigation also did not detect an influence of inflammation, as defined by CRP blood levels, on serum concentrations of citalopram or venlafaxine [ 33 ]. However, overall few studies have addressed the relationship of cytokines, antidepressants and drug metabolism, limiting the transferability of the aforementioned results in the context of affective disorders and antidepressant treatment.…”
Section: The Influence Of Cytokines On Pharma-
Cokinetics and -Dynamimentioning
confidence: 99%